Application Analysis of Internet of Things Technology in Large Chain Stores. Issue 1 (April 2021) - Huo, Xia
Abstract: The application of the Internet of Things technology in large chain stores can not only accurately locate the location of the goods, understand the information of the goods, and improve the business efficiency of mall operators, but also help consumers quickly find the items they need. At the same time, this can also reduce unnecessary cashier queuing time and help increase the attractiveness and competitiveness of the store. Based on this, this article will analyze how to use the Internet of Things to realize the operation and management of intelligent large-scale chain stores based on the analysis of related concepts. This article studies how to use the Internet of Things business management system to improve business levels and improve operating conditions.